A comparison of pregnancy rate between natural cycle and hormone replacement cycle in patients who underwent frozen embryo transfer using 2 consecutive hormone replacement regiments: A STROBE-compliant retrospective study. Issue 37 (11th September 2020) - Pang, Conghui; Guo, Lin; Bi, Yanyan; Wang, Kehua; Lian, Fang; Wu, Zhijuan; Xu, Xiaoyan; Sun, Zhengao
Abstract : Abstract: For frozen embryo transplantation patients who failed to use hormone replacement cycle (HRC) transplantation for 2 consecutive times, the third time of transplantation was divided into 2 groups: HRC and natural cycle (NC), and the pregnancy rate of the 2 groups, especially the clinical pregnancy rate, was compared. Retrospective study of 174 patients in the reproductive medicine center of an affiliated hospital of Shandong University of Traditional Chinese Medicine between January 2015 and September 2018. The 174 patients were all infertile with regular menstruation. They had undergone 2 consecutive failed cycles of endometrial preparation with hormone replacement therapy and prepare for the third frozen embryo transplantation. A third cycle of treatment was planned using either NC or HRC for endometrial preparation. All the embryos were obtained during the same oocyte retrieval cycle. Patients were divided into groups based on the method of endometrial preparation: 98 were classified as NC and 76 as HRC. The pregnancy outcomes for the 2 groups were compared. Confounding factors that may affect clinical pregnancy rates were analyzed. We found that on the day of endometrial transformation, estrogen levels and endometrial thickness in the NC group were significantly higher than those in the HRC group. There were no significant differences in the rates of biochemical pregnancy, clinical pregnancy, cumulative pregnancy, miscarriage, multiple pregnancy, ectopic pregnancy, or live birth between the 2 groups. It is concluded by binary regression analysis that the different endometrial preparation protocol have no significant effect on the CPR. NC is as effective as HRC after 2 previous cycles of HRC. Because this was a retrospective study design, selection bias is possible, although the baseline characteristics of the 2 groups of patients were matched.